2021
DOI: 10.3390/ijms222111980
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Achiral Liquid Crystalline Polymers for Chiral Self-Recovery

Abstract: Flexible construction of permanently stored supramolecular chirality with stimulus-responsiveness remains a big challenge. Herein, we describe an efficient method to realize the transfer and storage of chirality in intrinsically achiral films of a side-chain polymeric liquid crystal system by combining chiral doping and cross-linking strategy. Even the helical structure was destroyed by UV light irradiation, the memorized chiral information in the covalent network enabled complete self-recovery of the original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 149 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…3c). 41,42,56 Besides, the shoulder peak at 286.3 eV in C 1s X-ray photoelectron spectroscopy (XPS) spectrum disappeared after cross- Please do not adjust margins Please do not adjust margins linking (Fig. S4), which means that the C-OH in polymer terminal had been completely transformed into C-O-C.…”
Section: Resultsmentioning
confidence: 99%
“…3c). 41,42,56 Besides, the shoulder peak at 286.3 eV in C 1s X-ray photoelectron spectroscopy (XPS) spectrum disappeared after cross- Please do not adjust margins Please do not adjust margins linking (Fig. S4), which means that the C-OH in polymer terminal had been completely transformed into C-O-C.…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] Our group demonstrated that chiral molecules designed newly work as effective dopants in Ch*LCP, allowed for the supramolecular chiroptical induction and long‐term memory. [ 21 ] However, the construction of Ch*LC polymers often requires the use of expensive and/or environmentally unfavorable dopants. In this regard, naturally‐occurring chiral bio‐resources and semi‐synthetic derivatives are promising to afford inexpensive, renewable, and environmentally friendly, and greener chirality inducible scaffolds.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…20 Our group demonstrated that chiral molecules designed newly work as effective dopants in Ch*LCP, allowed for the supramolecular chiroptical induction and long-term memory. 21 However, the construction of Ch*LC polymers often requires the use of expensive and/or environmentally unfavorable dopants. In this regard, naturally-occurring chiral bioresources and semi-synthetic derivatives are promising to afford inexpensive, renewable, and environmentally friendly, and greener chirality inducible scaffolds.…”
Section: Background and Originality Contentmentioning
confidence: 99%